Un'ermeneutica del soggetto vivente Ricoeur lettore di Spinoza - De Carolis, Francesco (Fuori collana, 2024)
Paul Ricoeur, in his philosophical itinerary throughout the 20th century, analysed the major ontological, moral and linguistic issues that animated the philosophical, social and political debate in Europe. In this investigation, the French philosopher has always been confronted with the philosophy of Spinoza, whom he saw as a philosopher of life and man in his complex and sometimes mysterious situation. This approach is central to the question of the phenomenological search for the meaning of being in the world and with others.